Fresno County Young Lawyers Association Breakfast Board Meeting at Golden State Plaza Coffee Shop - Watkins, Howard::::::::: (1984)
In-coming Fresno County Young Lawyers Association President Debra Kazanjian thanking out-going Fresno County Young Lawyers Association President Herbert Levy